2008
DOI: 10.1089/ars.2008.2089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Clinical Implications of Reversible ProteinS-Glutathionylation

Abstract: Sulfhydryl chemistry plays a vital role in normal biology and in defense of cells against oxidants, free radicals, and electrophiles. Modification of critical cysteine residues is an important mechanism of signal transduction, and perturbation of thiol-disulfide homeostasis is an important consequence of many diseases. A prevalent form of cysteine modification is reversible formation of protein mixed disulfides (protein-SSG) with glutathione (GSH). The abundance of GSH in cells and the ready conversion of sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
518
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(546 citation statements)
references
References 347 publications
9
518
1
4
Order By: Relevance
“…Glutathione (GSH) is the most abundant non-protein cellular antioxidant, which together with its corresponding disulfide, GSH disulfide (GSSG), modulates intracellular redox status (Mieyal et al, 2008;Townsend, 2007). Both oxidative and nitrosative stresses lead to changes in the ratio of GSH-GSSG and thereby cause posttranslational modifications on redox-sensitive cysteine residues that include S-glutathionylation, S-nitrosylation, or S-oxidation of cellular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione (GSH) is the most abundant non-protein cellular antioxidant, which together with its corresponding disulfide, GSH disulfide (GSSG), modulates intracellular redox status (Mieyal et al, 2008;Townsend, 2007). Both oxidative and nitrosative stresses lead to changes in the ratio of GSH-GSSG and thereby cause posttranslational modifications on redox-sensitive cysteine residues that include S-glutathionylation, S-nitrosylation, or S-oxidation of cellular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that changes in the thiol redox state of the cell might affect the posttranslational modification of p65, including the phosphorylation of critical residues shown to contribute to the nuclear import of this molecule [33,34] . Moreover, a recent study has revealed that a number of redox-sensitive transcription factors are modified by GSH and thereby inhibit their function [35] . The p65 modification by GSH is thus implicated as an inhibitory mechanism by which carnosol regulates NF-κB activation through the increase in GSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Glutaredoxin (Grx) is suggested to be a major deglutathionylation enzyme in mammalian cells (74,76). The mammalian cytosolic form of Grx (Grx1) is very selective and effective for protein-SSG compared with other forms of disulfides (e.g., S-S disulfide bond, S-nitrosylation, etc.…”
Section: Deglutathionylation Enzymesmentioning
confidence: 99%
“…Oxidative stress, or reactive oxygen species (ROS), facilitates S-glutathionylation. Protein S-glutathionylation has been extensively discussed in many excellent reviews with a variety of different emphases (31,44,45,75,76,88,93,100,107). Over the past few years, S-glutathionylation has been increasingly observed in many ion channels, such as voltage-gated calcium channels, ryanodine receptor (RyR), and ATP-sensitive potassium channels (K ATP channels), all of which contribute to critical cellular functions (4,123,137,138).…”
Section: Introductionmentioning
confidence: 99%